Android-Based Practical Applications in Educational Evaluation - Kainde, Quido Conferti; Tambingon, Henny Nikolin; Rawis, Joulanda A. M.; Mangantes, Meisie Lenny (JR Education, 2022)
The purpose of the researchers in making this literature review is to obtain information related to the use of android-based practical applications in educational evaluation so that they can be implemented at Manado State University. The method in making this study uses a systematic literature review approach which requires researchers to use scientific-based findings literature. Based on the studies that have been carried out by the researcher, some information is obtained regarding the use of practical android-based applications that are suitable for use in educational evaluations, including (1) the Quizzme application for evaluating android-based student learning at the junior high school level, (2) the Application for Assessment of Productive Subject Practices for Vocational High School Students Android-based at SMK 45 Wonosari, (3) Android-based sign language learning and evaluation. These three studies are suitable to be applied in educational evaluation at Manado State University to replace PBT which is not effective for use today